2022
DOI: 10.1097/bsd.0000000000001295
|View full text |Cite
|
Sign up to set email alerts
|

Could Machine Learning Better Predict Postoperative C5 Palsy of Cervical Ossification of the Posterior Longitudinal Ligament?

Abstract: Study Design: This was a retrospective cohort study. Objective: The objective of this study was to investigate whether machine learning (ML) can perform better than a conventional logistic regression in predicting postoperative C5 palsy of cervical ossification of the posterior longitudinal ligament (OPLL) patients. Summary of Background Data: C5 palsy is one of the most common postoperative complications after surgical treatment of OPLL, with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…McGrit et al [ 88 ] examined data from 750 to 1,200 patients undergoing low back surgery and used regression analysis to predict the Oswestry Disability Index 1 year after surgery with an accuracy of up to 84%. Kim et al [ 89 ] observed the incidence of postoperative C5 palsy in patients with OPLL and reported superior efficacy of ML algorithms with logistic regression models in the prediction of C5 palsy. Several similar studies using ML algorithms have reported outcome prediction following cervical and lumbar spine surgeries [ 90 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…McGrit et al [ 88 ] examined data from 750 to 1,200 patients undergoing low back surgery and used regression analysis to predict the Oswestry Disability Index 1 year after surgery with an accuracy of up to 84%. Kim et al [ 89 ] observed the incidence of postoperative C5 palsy in patients with OPLL and reported superior efficacy of ML algorithms with logistic regression models in the prediction of C5 palsy. Several similar studies using ML algorithms have reported outcome prediction following cervical and lumbar spine surgeries [ 90 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since ML algorithms are increasingly being used in medical fields, several other studies have applied ML to validate the aspects of OPLL. For example, ML can predict C5 nerve palsy after cervical OPLL and to predict postoperative improvement of OPLL 14 , 41 . We collected 775 cervical spine surgery patients’ data and 84 complete variables to screen out relevant characteristics of cervical OPLL and construct a diagnostic model.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, the development of AI, LLMs, and GPTs has significantly impacted the field of neurosurgery and spinal care as well. [1][2][3][4][5] Zaidat et al 6 studied performance of a LLM in the generation of clinical guidelines for antibiotic prophylaxis in spine surgery. This study delves into the capabilities of ChatGPT's models, GPT-3.5 and GPT-4.0, showcasing their potential to streamline medical processes.…”
mentioning
confidence: 99%